Transformation of the Risk Management Role from Second Line to One Point Five Line of Defense in Supporting Corporate Governance, Value Protection, and Value Creation: A Case Study of Implementation in an Indonesian Oil and Gas Company - Evalina Sitepu; Edo Prehandhika (Journal of Social Research, 2026)
Oil and Gas corporation operates within a highly complex energy value chain, exposing the company to strategic, operational, financial, and market risks. These dynamics underscore the need for a risk management function that not only protects value but also supports value creation in line with ISO 31000:2018 principles. This study examines the transformation of the risk management function from a traditional Second Line into a One Point Five Line model, introduced to address governance gaps and comply with UU No. 40 Tahun 2007. Using a qualitative case study approach, data were collected through in-depth interviews with key informants and document analysis focusing on the application of the Four Eyes Principle in investment, hedging, and credit processes. The results reveal that the transformation significantly enhances the integration of risk considerations into strategic decision-making. The involvement of the risk management function in investment, hedging, and credit committees strengthens oversight, improves alignment with corporate risk appetite, and increases accountability across organizational lines. The model also fosters more transparent documentation and higher-quality risk analysis, contributing to a more disciplined and data-driven decision-making process. Overall, the One Point Five Line model proves effective in improving internal controls while ensuring a balanced approach between value protection and value creation. These findings offer practical insights for state-owned enterprises and energy companies seeking to strengthen risk governance in increasingly complex business environments.